Gender: The Hidden God in Yasmina Reza's Le Dieu du Carnage - Lauren Tilger (Studies in 20th & 21st Century Literature, 2016)
Most critics have analyzed acclaimed playwright Yasmina Reza’s Le Dieu du Carnage (2007) as a descent into savagery. This close examination of the play points to the role of gender norms and stereotypes in causing the decline in civility. By taking part in a culture that worships gender ideals, the characters in Reza’s play police one another’s actions to ensure that everyone behaves like proper men and women. The act of attempting to successfully perform femininity or masculinity leads to the evening’s disastrous events. In contrast with readings that have erased gender from the power dynamics of the play and its depiction of conflict, this article reveals the God of Carnage to be gender.
Keywords: Carnage; Le Dieu du Carnage; Yasmina Reza; gender